ANALISIS PENGARUH FIRM SIZE, DER, DAN SALES GROWTH TERHADAP DIVIDEND PAYOUT RATIO DENGAN ROE SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN NON KEUANGAN YANG LISTED DI BEI TAHUN 2009-2011 - KAUTSAR, ACHMAD (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2014)
AbstractThis research studies the relation between Firm Size, DER, Sales Growth, and ROE on Dividend Payout Ratio all non financial firms which listed in the Indonesian Stock Exchange from 2009-2011. Dividend payout has been an issue of interest in financial literature. The problems in this research is still have an inconsistency of data empirical phenomena and still found a gap research that examines the Dividend Payout Ratio which is measured by Firm Size, Debt Equity Ratio, and Sales Growth. moreover, this research try to test ROE as an intervening variable.In this research using the technique of path analysis with AMOS. Sampling technique used here is purposive sampling, and from the 461 listed companies, only 77 companies that can be sampled. Before using the path analysis, we must do the test assumption of normality and outliers.The research found a significant positive relations Firm Size and ROE on DPR, as well as a significant positive relations Firm Size and Sales Growth on ROE. The research also found a significant negative relationship DER on DPR. However, this research has found no significant effect Sales Growth on DPR, as well as in relation DER on ROE. ROE was found able to be intervening variables for influence of Firm Size on DPR. While in the test influence of DER and Sales Growth on DPR, ROE can’t be intervening variable.